Schrödinger operators with non-symmetric zero-range potentials
Non-self-adjoint Schrödinger operators A_T which correspond to non-symmetric zero-range potentials are investigated. For a given A_T , a description of non-real eigenvalues, spectral singularities and exceptional points are obtained; the possibility of interpretation of A_T as a self-adjoint operator in a Krein space is studied, the problem of similarity of A_T to a self-adjoint operator in a Hilbert space is solved., number=1, journal=Methods of Functional Analysis and Topology, author=Kuzhel, S. A. and Grod, A., year=2014, month=Mar., pages=34–49